Severe Cutaneous Reactions Requiring Hospitalization in Allopurinol Initiators: A Population‐Based Cohort Study. Issue 4 (28th March 2013) - Kim, Seoyoung C.; Newcomb, Craig; Margolis, David; Roy, Jason; Hennessy, Sean
Abstract Objective Rare but potentially life‐threatening cutaneous adverse reactions have been associated with allopurinol, but population‐based data on the incidence and mortality of such reactions are scarce. Methods We conducted a propensity score–matched cohort study to evaluate the incidence rate (IR) and in‐hospital mortality of hospitalization for severe cutaneous adverse reactions (SCARs) in allopurinol initiators compared to non–allopurinol users, using data from 5 large Medicaid programs. The primary outcome was identified by the principal discharge diagnosis code 695.1. A Cox proportional hazards model evaluated the relative risk of SCARs associated with the use of allopurinol and determined the relative risk of SCARs associated with allopurinol dose. Results During a followup period of 65, 625 person‐years for allopurinol initiators, 45 were hospitalized with SCARs. The crude IR was 0.69 (95% confidence interval [95% CI] 0.50–0.92) per 1, 000 person‐years. All 45 cases occurred within 365 days and 41 (91.1%) occurred within 180 days after initiating treatment with allopurinol. Twelve patients (26.7%) died during the hospitalization. The crude IR in non–allopurinol users was 0.04 (95% CI 0.02–0.08) per 1, 000 person‐years. The risk of SCARs was increased in allopurinol initiators versus nonusers (hazard ratio [HR] 9.68, 95% CI 4.55–20.57). Among allopurinol initiators, the HR for high‐dosage (>300 mg/day) versus low‐dosage allopurinol was 1.30 (95% CI 0.31–5.36) after adjusting for age, comorbidities, and recent diuretic use. Conclusion Among allopurinol initiators, SCARs were found to be rare but often fatal, and occurred mostly in the first 180 days of treatment. The risk of SCARs was 10 times as high in allopurinol initiators as compared to allopurinol nonusers.